COMPARATIVE LITERATUREOF NOVEL SURAT KECIL UNTUK TUHANAND OSCARAND THE LADY IN PINK - Andri Noryunita; Dewi Purwatiningsih (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
Comparative study is the way to make comparison of two (possibly more) things. In  literature,  there  are  some  aspects  that  could be  compared  such  as  the  literary work  itself. This  study discusses about  two  literary works  from different  culture and different author. The first one is novel which title Surat Kecil Untuk Tuhan by Agnes  Devauner  and  the  second  is  short  story  from  Eric-Emmanuel  Schmitt which  title Oscar and  the Lady  in Pink. The purpose of  this study  is  to compare about the intrinsic elements of both literary works and to compare about the main character  there.  The method which  is  used  to  this  study  is  qualitative  research because  of  the  data  collected  by  the  word  or  sentence  but  not  the  number. Qualitative  data  deals  with  descriptions  which  could  be  observed  and  not measured.  The  results  of  this  study  showed  to  the  reader  about  the  intrinsic elements  of  both  different  literary works  and  also  the  comparison  between  the main characters of each literary work. Hopefully this study will give the beneficial to the reader in terms of comparative study.